Selective imaging modalities after first pyelonephritis failed to identify significant urological anomalies, despite normal antenatal ultrasounds. (22nd May 2017) - Mola, Gylli; Wenger, Therese Ramstad; Salomonsson, Petra; Knudsen, Inge Jenny Dahl; Madsen, Jan Lysgaard; Møller, Søren; Olsen, Beth Härstedt; Vinicoff, Pablo Gustavo; Thorup, Jorgen; Cortes, Dina
Abstract: Aim: We investigated the consequences of applying different imaging guidelines for urological anomalies after first pyelonephritis in children with normal routine antenatal ultrasounds. Methods: The cohort comprised 472 children treated for their first culture‐positive pyelonephritis and investigated with ultrasound and renal scintigraphy. We excluded patients with known urological anomalies and patients born before routine antenatal ultrasound. We followed the cohort for a median of 5.7 years (3.1–10.1 years) by reviewing their medical reports. Results: Urological anomalies were diagnosed in 95 patients. Dilated vesicoureteral reflux (VUR) was the predominant finding (n = 29), including nine who initially had surgery. Using imaging guidelines from the American Academy of Pediatrics would have missed 11 urological patients, including two with initial surgery, and avoided 339 scintigraphies. Using the European Association of Paediatric Urology guidance would have missed three urological patients, one with initial surgery, and avoided 46 scintigraphies. Investigating patients under two years with ultrasound and scintigraphy, and just ultrasound in children over two years, would have identified all patients initially treated with surgery and avoided 65 scintigraphies. Conclusion: Dilated VUR was the dominant anomaly in a cohort with first time pyelonephritis and normal antenatal ultrasound. The optimal imaging strategy after pyelonephritis must be identified.